ETIKA MEMODERASI PENGARUH KOMPETENSI, PENGALAMAN DAN INDEPENDENSI PADA KUALITAS HASIL PEMERIKSAAN INSPEKTORAT - Astrawan, I Kadek Yogi; Mimba, Ni Putu Sri Harta; Dwirandra, A. A. N. B. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 05.NO.06. TAHUN 2016, 2016)
This study is purpose to find empirical evidence about ability of ethics examiner moderating influence of competence, work experience and independence on the quality of the examination results Klungkung District Inspectorate. The data used in this study was obtained from the whole apparatus Inspectorate Klungkung regency. Data collected through questionnaires. The method of determining the data used is the method of census. The number of respondents in this research is 34 people. Data analysis method used is Moderated Regression Analysis (MRA). The results showed that the ethics examiner is unable to moderate the influence of competence on the quality of the examiner, but ethics examiner able to moderate the influence of work experience on the quality of the examination results. Research also shows that ethics examiner is unable to moderate the influence independency on the quality of the examination results.
Keywords: competence, experience, independence, ethics, the examination